2022
DOI: 10.3390/ma15238705
|View full text |Cite
|
Sign up to set email alerts
|

Nanotopography Evaluation of NiTi Alloy Exposed to Artificial Saliva and Different Mouthwashes

Abstract: Nitinol (NiTi) alloy is a widely used material for the production of orthodontic archwires. Its corrosion behavior in conditions that exist in the oral cavity still remains a great characterization challenge. The motivation behind this work is to reveal the influence of commercially available mouthwashes on NiTi orthodontic archwires by performing non-electrochemical corrosion tests and quantifying the changes in the nanotopography of commercially available NiTi orthodontic wires. In this study, we examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Overall, the effect of immersion in artificial saliva on morphological changes on NiTi surface was manifested primarily through the increased number of salt deposits. This result agrees well with the study of Bobić et al [51], where no significant changes were observed for NiTi surface roughness after 21 days of immersion.…”
Section: Niti Archwiressupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, the effect of immersion in artificial saliva on morphological changes on NiTi surface was manifested primarily through the increased number of salt deposits. This result agrees well with the study of Bobić et al [51], where no significant changes were observed for NiTi surface roughness after 21 days of immersion.…”
Section: Niti Archwiressupporting
confidence: 93%
“…The surface roughness is reported as the arithmetic average height parameter, S a , a commonly used parameter which, in general, provides a good description of height variations [70]. However, for examining the corrosion effects on larger areas (note that the results are reported for a 256 × 256 µm area), the S a parameter was found to be insufficient [51]; hence, the S dr parameter was also used. The S dr parameter denotes the developed interfacial area ratio, i.e., the percentage of additional surface area contributed by the texture as compared to an ideal plane the size of the measurement region.…”
Section: Surface Roughnessmentioning
confidence: 99%